Liquidity market support during the global crisis - Černohorský, Jan; Teplý, Petr; Vrábel, Michal (Univerzita Pardubice, 2010)
Liquidity risk management ranks to key concepts applied in finance. Liquidity is defined as a capacity to obtain funding when needed, while liquidity risk means as a threat to this capacity to generate cash at fair costs. In the paper we present liquidity market support during the global crisis in the 2007-2009 period and related regulatory challenges. We see five main regulatory liquidity risk management issues requiring revision in coming years: liquidity measurement, intra-day and intragroup liquidity management, contingency planning and liquidity buffers, liquidity systems, controls and governance, and finally models testing the viability of business liquidity models.
Keywords: liquidity; risk management; regulation; global crisis